Donor T cells for CAR T cell therapy - Tiffany C. Y. Tang; Ning Xu; Robert Nordon; Michelle Haber; Kenneth Micklethwaite; Alla Dolnikov (BMC, 2022)
Abstract Adoptive cell therapy using patient-derived chimeric receptor antigen (CAR) T cells redirected against tumor cells has shown remarkable success in treating hematologic cancers. However, wider accessibility of cellular therapies for all patients is needed. Manufacture of patient-derived CAR T cells is limited by prolonged lymphopenia in heavily pre-treated patients and risk of contamination with tumor cells when isolating T cells from patient blood rich in malignant blasts. Donor T cells provide a good source of immune cells for adoptive immunotherapy and can be used to generate universal off-the-shelf CAR T cells that are readily available for administration into patients as required. Genome editing tools such as TALENs and CRISPR-Cas9 and non-gene editing methods such as short hairpin RNA and blockade of protein expression are currently used to enhance CAR T cell safety and efficacy by abrogating non-specific toxicity in the form of graft versus host disease (GVHD) and preventing CAR T cell rejection by the host.